2018
DOI: 10.3847/1538-4357/aacd4c
|View full text |Cite
|
Sign up to set email alerts
|

Observations of the Electron Jet Generated by Secondary Reconnection in the Terrestrial Magnetotail

Abstract: We report in situ observations of an electron jet generated by secondary reconnection within the outflow region of primary reconnection in the terrestrial magnetotail by the Magnetospheric Multiscale (MMS) mission. The MMS spacecraft first passed through the primary X-line and then crossed the electron jet in the outflow of primary reconnection. There are a series of small-scale flux ropes in the secondary reconnection region. Decoupling from the magnetic field for both ions and electrons, an intense out-of-pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 36 publications
4
55
2
Order By: Relevance
“…The strong current is primarily carried by electrons, and thus, the energy dissipation in this event is driven by electrons. The magnitude of energy dissipation inside the electron jet (J · E′ ≈ −2 nW/m 3 ) is even stronger than that at dipolarization fronts, demonstrating the importance of the electron jet in converting/dissipating energy in the Earth's magnetotail, as suggested recently by Huang et al (2018). Both the current filaments and energy dissipation appear at the O-line structure, well supporting the proposition of Fu et al (2017).…”
Section: Summary and Discussionsupporting
confidence: 77%
“…The strong current is primarily carried by electrons, and thus, the energy dissipation in this event is driven by electrons. The magnitude of energy dissipation inside the electron jet (J · E′ ≈ −2 nW/m 3 ) is even stronger than that at dipolarization fronts, demonstrating the importance of the electron jet in converting/dissipating energy in the Earth's magnetotail, as suggested recently by Huang et al (2018). Both the current filaments and energy dissipation appear at the O-line structure, well supporting the proposition of Fu et al (2017).…”
Section: Summary and Discussionsupporting
confidence: 77%
“…Similar temperature anisotropy and bidirectional electron velocity distributions have been found in the inflow region of the diffusion region (Chen et al, 2009;Huang et al, 2018;Zhou et al, 2019). It is suggested that acceleration by parallel electric field causes the temperature anisotropy in the inflow region (Egedal et al, 2010).…”
Section: Journal Of Geophysical Research: Space Physicssupporting
confidence: 66%
“…An out-of-plane electron jet with peak V eM nearly 800 km/s was observed at this current sheet ( Figure 2c). This X line was either a secondary reconnection X line in the exhaust of a primary X line (Huang, Jiang, et al, 2018) or an X line pushed southward by a northward X line with faster reconnection rate in a multiple X line reconnection (Hasegawa et al, 2008;Hwang et al, 2018). Furthermore, V eL also exhibits an enhancement associated with the current sheet.…”
Section: Event Overviewmentioning
confidence: 99%